Theoretical And Practical Aspects Of Developing Students' Heuristic Thinking In Digital Education (Journal of Pedagogical Inventions and Practices, 2025)
This article analyzes in detail the issues of developing students' heuristic thinking in the context of digital learning. It shows the theoretical foundations of heuristic thinking, the possibilities of integration with digital tools, as well as the practical significance of such methods as the problem method, bainstorming, and the game approach. The article also highlights the role of digital learning platforms, virtual laboratories, and interactive applications in shaping students' creative search and thinking, as well as the specifics of assessment and reflection processes. The authors offer specific proposals to overcome obstacles such as problems related to digital infrastructure, the need to improve teachers' digital literacy, and student passivity. The final article contains scientific and practical recommendations for educating a generation of creative and independent thinkers by strengthening heuristic thinking in the modern education system